Correlation analysis of surgical outcomes and spino-pelvic parameters in patients with degenerative lumbar scoliosis - Zhou, Hang; Liang, Zhancheng; Li, Pengfei; Shi, Huihong; Liang, Anjing; Gao, Wenjie; Huang, Dongsheng; Peng, Yan (Frontiers in Surgery, 2024)
Objectives: The aim of the study is to analyze factors that affect the postoperative health related quality of life (HRQOL) of degenerative lumbar scoliosis (DLS) patients, and explore the appropriate pelvic incidence minus lumbar lordosis (PI-LL) value for Chinese DLS patients. Methods: DLS patients who met the inclusion and exclusion criteria were included in the study. Their general information, spino-pelvic parameters, and HRQOL were collected. Correlation analysis was used to explore the spino-pelvic parameters that affect the postoperative HRQOL. Thresholds of each parameter were obtained through the ROC curve. Regardless of the effect of age, DLS patients were classified into three groups according to the SRS-Schwab classification: group 0 means PI-LL<10°, group + means PI-LL=10-20°, group ++ means PI-LL>20°. Postoperative HRQOL was analyzed using variance methods. ROC curve was used to measure the appropriate PI-LL threshold. When considering the effect of age, the patients with ODI<75% percentile were considered to have a satisfying clinical outcome, which was drawn to an equation between PI-LL, age and PI by multiple linear regression equation. Results: A total of 71 patients were included. Compared to the control group, there were significant differences in both postoperative ODI and SRS-22 score when the postoperative Cobb angle ≤11°, postoperative lumbar lordosis index (LLI) >0.8, postoperative sagittal vertical axis (SVA) ≤5cm, postoperative T1 pelvic angle (TPA) ≤16° and postoperative global tilt (GT) ≤22°, respectively. Regardless of the effect of age, there was a statistical difference of postoperative HRQOL between group 0 and group ++. The PI-LL threshold derived from the ROC curve was 14.4°. Compared to PI-LL > 14° group, PI-LL ≤ 14° group achieved lower postoperative ODI score and higher postoperative SRS-22 score. Considering the influence of age, the equation for ideal PI-LL was PI-LL = 0.52age+0.38PI-39.4 (R=0.509, P=0.001). Conclusions: PI-LL was an important parameter that affects the postoperative HRQOL of DLS patients. Sufficient lumbar lordosis should be restored during the operation (LL≥PI-14°). The appropriate PI-LL value was affected by age. Smaller lumbar lordosis needed to be restored as the age increased.